2020
DOI: 10.1101/2020.08.20.20174912
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Longitudinal analysis of virus load, serum antibody levels and virus neutralizing activity in vitro in cases with less severe COVID-19

Abstract: Background: Patients infected with SARS-CoV-2 exhibit a highly variable clinical course, varying from barely discernible signs of disease, to moderate flu-like symptoms and, occasionally, with life-threatening pneumonia and/or cytokine storm. The relationship between the nasopharyngeal virus load, IgA and IgG antibodies to both the S1-RBD-protein and the N-protein as well the neutralizing activity (NAbs) against SARS-CoV-2 in the blood of moderately afflicted COVID-19 patients has not been investigated longitu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…21 In less severe cases, nAb in serum reached a peak about 4 weeks after disease onset but dropped to a lower level about 6 weeks later. 78 An earlier IgG antibody response against the S2 domain of the S protein could better mediate virus neutralization, as previously suggested for SARS-CoV-1 nAb targeting the S2 domain. 26,[79][80][81] Analyses at a 1-month interval on 31 convalescent individuals showed that RBDspecific IgG slightly decreased between 6 and 10 weeks after symptoms onset but RBD-specific IgM decreased much more abruptly.…”
Section: Nab Declinementioning
confidence: 72%
See 1 more Smart Citation
“…21 In less severe cases, nAb in serum reached a peak about 4 weeks after disease onset but dropped to a lower level about 6 weeks later. 78 An earlier IgG antibody response against the S2 domain of the S protein could better mediate virus neutralization, as previously suggested for SARS-CoV-1 nAb targeting the S2 domain. 26,[79][80][81] Analyses at a 1-month interval on 31 convalescent individuals showed that RBDspecific IgG slightly decreased between 6 and 10 weeks after symptoms onset but RBD-specific IgM decreased much more abruptly.…”
Section: Nab Declinementioning
confidence: 72%
“…In most of Covid‐19 inpatients, nAb reached a plateau 2 weeks post‐symptom onset and then declined, reaching a low or undetectable level ≥40 days post‐symptom onset 21 . In less severe cases, nAb in serum reached a peak about 4 weeks after disease onset but dropped to a lower level about 6 weeks later 78 . An earlier IgG antibody response against the S2 domain of the S protein could better mediate virus neutralization, as previously suggested for SARS‐CoV‐1 nAb targeting the S2 domain 26 ,.…”
Section: Introductionmentioning
confidence: 99%